Peroxisome Proliferator‐Activated Receptor α Activation Suppresses Cytochrome P450 Induction Potential in Mice Treated with Gemfibrozil. Issue 3 (10th May 2017) - Shi, Cunzhong; Min, Luo; Yang, Julin; Dai, Manyun; Song, Danjun; Hua, Huiying; Xu, Gangming; Gonzalez, Frank J.; Liu, Aiming
Abstract: Gemfibrozil, a peroxisome proliferator‐activated receptor α (PPARα) agonist, is widely used for hypertriglyceridaemia and mixed hyperlipidaemia. Drug–drug interaction of gemfibrozil and other PPARα agonists has been reported. However, the role of PPARα in cytochrome P450 (CYP) induction by fibrates is not well known. In this study, wild‐type mice were first fed gemfibrozil‐containing diets (0.375%, 0.75% and 1.5%) for 14 days to establish a dose–response relationship for CYP induction. Then, wild‐type mice and Ppar α‐null mice were treated with a 0.75% gemfibrozil‐containing diet for 7 days. CYP3a, CYP2b and CYP2c were induced in a dose‐dependent manner by gemfibrozil. In Ppar α‐null mice, their mRNA level, protein level and activity were induced more than those in wild‐type mice. So, gemfibrozil induced CYP, and this action was inhibited by activated PPARα. These data suggested that the induction potential of CYPs was suppressed by activated PPARα, showing a potential role of this receptor in drug–drug interactions and metabolic diseases treated with fibrates.